CERITA RAKYAT BIAK SEBAGAI SASTRA ANAK UNTUK TINGKAT SD - Muntihanah NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Biak regency has many variaties of fairy tale in which a moral values, a strong work ethos, and a live philosophy. Unfortunately, this potential has not been used optimally as a reference of kid reading literature for primary school. This paper aims to know the potential of the “Asal Mula Ikan Saling Memangsa” fairytale as kid reading literature. The criterion based on three criteria, namely the simplicity of structure; the character value; and the correlation between the structure of story and the developmental of kid intelligence. Data analysis uses theory of structural; theory of developmental intelligence; and character value. It is concluded that “Asal Mula Ikan Saling Memangsa” fairytale is recommended to be kid reading of 7-11 years old because the story has a simple structure. The simplicity of structure reflected on the linear plot, the flat character, the very simple setting, the limited problems, and the limited characters and theirs relations. The simplicity is also found in the disclosure of a story that is not abstract, the uses of the form of base word which dominant, and the use of the phrase that generally uses similar compound sentences. The value of the character that contain in this story related with ourself that are responsible and discipline.